2022
DOI: 10.1002/cam4.5440
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness of first‐line versus second‐line use of domestic anti‐PD‐1 antibody sintilimab in Chinese patients with advanced or metastatic squamous non‐small cell lung cancer

Abstract: Background Programmed cell death protein‐1/programmed cell death ligand‐1 (PD‐1/L1) inhibitor is a promising therapeutic option that can be used as either a first‐line or second‐line treatment for driver‐negative advanced or metastatic squamous non‐small cell lung cancers (sqNSCLC). However, reuse of PD‐1/L1 inhibitor in second‐line beyond progression after the first‐line is generally not recommended. Therefore, oncologists face challenges in making a proper decision of using PD‐1/L1 inhibitor. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Results from Cheng 2022 [ 45 ] showed that sintilimab retained for second-line use had a higher efficacy and medical cost than first-line treatment (US $12,203 vs. US $14,045), with a corresponding ICER of $12,693 /QALY, which was cost-effective.…”
Section: Resultsmentioning
confidence: 99%
“…Results from Cheng 2022 [ 45 ] showed that sintilimab retained for second-line use had a higher efficacy and medical cost than first-line treatment (US $12,203 vs. US $14,045), with a corresponding ICER of $12,693 /QALY, which was cost-effective.…”
Section: Resultsmentioning
confidence: 99%
“…Some of these medications have been included in NEMF, which has greatly improved the accessibility and affordability of therapy for patients. This expansion of treatment options has increased patient satisfaction and met the demand for cancer medications 16–18 . Details of the time of approval, indications, and other relevant information were provided in Table S2.…”
Section: Discussionmentioning
confidence: 99%
“…This expansion of treatment options has increased patient satisfaction and met the demand for cancer medications. 16 , 17 , 18 Details of the time of approval, indications, and other relevant information were provided in Table S2 .…”
Section: Discussionmentioning
confidence: 99%
“…Other cancer-related management costs, including routine follow-up costs, best supportive care and terminal care costs, were obtained from published studies as with previous economic evaluations in China. 23 , 24 …”
Section: Methodsmentioning
confidence: 99%